2021
DOI: 10.1038/s41467-021-21260-x
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic frequency-modulated continuous-wave terahertz spectroscopy with 4 THz bandwidth

Abstract: Broadband terahertz spectroscopy enables many promising applications in science and industry alike. However, the complexity of existing terahertz systems has as yet prevented the breakthrough of this technology. In particular, established terahertz time-domain spectroscopy (TDS) schemes rely on complex femtosecond lasers and optical delay lines. Here, we present a method for optoelectronic, frequency-modulated continuous-wave (FMCW) terahertz sensing, which is a powerful tool for broadband spectroscopy and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 37 publications
0
62
0
Order By: Relevance
“…A measured standard deviation of 40 nm was recently reported by Molter et al 26 employing such a system. Although Liebermeister et al have recently reported a CW system with a bandwidth 4 THz 24 , using such huge bandwidth will also immensely increase the overall scan duration for the proposed single-pixel based imaging system. Last but not least, no multi-layer structures were characterized.…”
Section: Resultsmentioning
confidence: 99%
“…A measured standard deviation of 40 nm was recently reported by Molter et al 26 employing such a system. Although Liebermeister et al have recently reported a CW system with a bandwidth 4 THz 24 , using such huge bandwidth will also immensely increase the overall scan duration for the proposed single-pixel based imaging system. Last but not least, no multi-layer structures were characterized.…”
Section: Resultsmentioning
confidence: 99%
“…With this FDS system, a PET film with a thickness of 23 µm could be measured with an accuracy better than 2%, which corresponds to an uncertainty below 0.5 µm. This demonstrates that FDS can compete with TDS for accurate thickness measurements on thin dielectric layers [10]. Thereby, the main advantage of FDS compared to TDS is the simplicity of its system architecture.…”
Section: Introductionmentioning
confidence: 91%
“…Meta-and nanomaterials with various unit cell geometries working in the THz region are an emerging option assuring much promise for on-site, high-speed virus detection and have the potential to go beyond the detection limit. Moreover, with recent advancements in miniaturized THz technologies [86][87][88][89][90], THz-based virus sensing platforms can be widely deployed, even to remote locations. Even though terahertz based biosensing methods have been used for several sectors [91,92], there is still a need for extensive research on SARS CoV-2 and similar virus detection.…”
Section: Challenges and Future Trends Of Thz-based Sensingmentioning
confidence: 99%